O‘ZBEK TILIDAGI “DO‘PPI” LEKSEMASI ISHTIROK ETGAN MILLIY-MADANIY BO ‘YOQDORLIKGA EGA FRAZEOLOGIK IBORALARNING TAHLILI (Journal of Universal Science Research, 2025)
Phraseological units in the Uzbek language reflect the national spirit and the life experiences of the people. The word “do‘ppi” (traditional Uzbek skullcap) is one of the key components in such phraseological expressions. It appears in numerous idioms, reflecting the cultural and social characteristics of the Uzbek people. This article analyzes phraseological units containing the word “do‘ppi,” exploring their meanings, usage contexts, and national features. These expressions not only highlight the richness of the Uzbek language, but also embody the way of life and values of the nation.